Odpowiedź:
[tex]A.\ \ (2\cdot10^4)\cdot(2\cdot10^2)=(2\cdot2)\cdot(10^4\cdot10^2)=4\cdot10^{4+2}=4\cdot10^6\\\\\\B.\ \ 2,5\cdot10^5+1,5\cdot10^3=2,5\cdot10^2\cdot10^3+1,5\cdot10^3=(2,5\cdot10^2+1,5)\cdot10^3=\\\\=(2,5\cdot100+1,5)\cdot10^3=(250+1,5)\cdot1000=251,5\cdot1000=251500=2,515\cdot10^5[/tex]
[tex]C.\ \ 6,2\cdot10^{20}-2,2\cdot10^{12}=6,2\cdot10^8\cdot10^{12}-2,2\cdot10^{12}=(6,2\cdot10^8-2,2)\cdot10^{12}=\\\\=(6,2\cdot100000000-2,2)\cdot10^{12}=(620000000-2,2)\cdot10^{12}=619999997,8\cdot10^{12}=\\\\=6,199999978\cdot10^{20}[/tex]
[tex]D.\ \ \frac{2,8\cdot10^1^1}{0,7\cdot10^3}=\frac{2,8}{0,7}\cdot\frac{10^1^1}{10^3}=4\cdot10^{11-3}=4\cdot10^8[/tex]